Digital Wellbeing: Considering Self-transcendence - Kitson, Alexandra; Riecke, Bernhard E.; Gaggioli, Andrea (ACM, 2019)
Technology for supporting wellbeing has long been an aim for many disciplines, including computer science, psychology, and human-computer interaction. However, the definition of wellbeing is not always clear and this has implications for how we design for and assess technologies that aim to foster it. Here, we discuss current definitions of wellbeing and how it correlates with and sometimes is an outcome of self-transcendence. We then focus on how technologies can support wellbeing through experiences of self-transcendence, ending with possible future directions.
Keywords: NSERC DG 2026; Riecke; Riecke_2019; alex-kitson; andrea-gaggioli; awe; bernhard-riecke; conferencePaper; conferencePapers; earthgazing; transformative experience design; type: workshop paper